Ankle kinematics and ground reaction force during single leg drop landing in sports participants with chronic groin pain - Harwin, Lauren Sandra (Stellenbosch : Stellenbosch University, 2014)
Thesis (MScPhysio)--Stellenbosch University, 2014.